2021
DOI: 10.1038/s41598-021-92295-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of image generation by quantum annealer

Abstract: Quantum annealing was originally proposed as an approach for solving combinatorial optimization problems using quantum effects. D-Wave Systems has released a production model of quantum annealing hardware. However, the inherent noise and various environmental factors in the hardware hamper the determination of optimal solutions. In addition, the freezing effect in regions with weak quantum fluctuations generates outputs approximately following a Gibbs–Boltzmann distribution at an extremely low temperature. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…degenerate states is the introduction of parallel tempering with isoenergetic cluster updates in Monte Carlo methods 16 or the combination with simulated annealing on a quantum annealer 17,18 . We mention that Boltzmann machines, which can serve as a link between machine learning and statistical thermodynamics 19 , are investigated in the context of QA [20][21][22][23] from a computer science perspective, but to the best of our knowledge, the direct application of QA for classical finite temperature modeling for statistical physics and materials science has not yet been accomplished and is the subject of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…degenerate states is the introduction of parallel tempering with isoenergetic cluster updates in Monte Carlo methods 16 or the combination with simulated annealing on a quantum annealer 17,18 . We mention that Boltzmann machines, which can serve as a link between machine learning and statistical thermodynamics 19 , are investigated in the context of QA [20][21][22][23] from a computer science perspective, but to the best of our knowledge, the direct application of QA for classical finite temperature modeling for statistical physics and materials science has not yet been accomplished and is the subject of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum effect on the case with multiple optimal solutions has also been discussed 35 , 36 . Further, applications of quantum annealing for machine learning for solving optimization problems have been reported 37 42 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of the quantum annealer to combinatorial optimization problems has been widely studied. [19][20][21][22][23][24][25][26][27][28][29][30][31] The quantum effect on the degenerate ground state has also been investigated. 32,33) Several studies have reported sampling applications of quantum annealing to machine learning.…”
Section: Introductionmentioning
confidence: 99%